Analysis of Pregnancy Outcomes in Women with Polycystic Ovary Syndrome (PCOS): A Retrospective Study - Manjula Salgotra; Nancy Bharti; Varsha Sinha; Rahul Tiwari; Heena Dixit Tiwari; Chapala Shashank; Jasmine Kalsi; Priyanka R Pujari (Wolters Kluwer Medknow Publications, 2024)
Introduction: Although PCOS affects reproductive health, its consequences on the outcome of pregnancies are still up for discussion. Comparing the pregnancy outcomes of women with PCOS to a control group was the goal of this retrospective research. Methods: Analysis of data from tertiary care centers between 2017 and 2022 was done in retrospective. While the controls (n = 300) matched for age, BMI, and parity, the PCOS group (n = 300) satisfied Rotterdam criteria. Maternal-fetal health, birth outcomes, and gestational problems were evaluated. Results: Compared to controls, women with PCOS had a greater incidence of preeclampsia (12.3% vs. 8.1%, P = 0.023) and gestational diabetes (18.7% vs. 9.8%, P < 0.001). On the other hand, there were no notable variations in low birth weight (P = 0.589) or preterm delivery (P = 0.321). Conclusion: In summary, the correlation between PCOS and increased risks of gestational diabetes and preeclampsia emphasizes the necessity of customized therapies. The intricacy of PCOS's influence on birth outcomes is shown by the inconclusive results regarding preterm delivery and low birth weight, which call for more research to enhance mother and newborn health in this group.